High-resolution array copy number analyses for detection of deletion, gain, amplification and copy-neutral LOH in primary neuroblastoma tumors: Four cases of homozygous deletions of the CDKN2A gene - Kogner Per; Abrahamsson Jonas; Sjöberg Rose-Marie; Enerbäck Charlotta; Olsson Linda; Erichsen Jennie; Carén Helena; Martinsson Tommy (BMC Genomics, 2008)
Abstract Background Neuroblastoma is a very heterogeneous pediatric tumor of the sympathetic nervous system showing clinically significant patterns of genetic alterations. Favorable tumors usually have near-triploid karyotypes with few structural rearrangements. Aggressive stage 4 tumors often have near-diploid or near-tetraploid karyotypes and structural rearrangements. Whole genome approaches for analysis of genome-wide copy number have been used to analyze chromosomal abnormalities in tumor samples. We have used array-based copy number analysis using oligonucleotide single nucleotide polymorphisms (SNP) arrays to analyze the chromosomal structure of a large number of neuroblastoma tumors of different clinical and biological subsets. Results Ninety-two neuroblastoma tumors were analyzed with 50 K and/or 250 K SNP arrays from Affymetrix, using CNAG3.0 software. Thirty percent of the tumors harbored 1p deletion, 22% deletion of 11q, 26% had MYCN amplification and 45% 17q gain. Most of the tumors with 1p deletion were found among those with MYCN amplification. Loss of 11q was most commonly seen in tumors without MYCN amplification. In the case of MYCN amplification, two types were identified. One type displayed simple continuous amplicons; the other type harbored more complex rearrangements. MYCN was the only common gene in all cases with amplification. Complex amplification on chromosome 12 was detected in two tumors and three different overlapping regions of amplification were identified. Two regions with homozygous deletions, four cases with CDKN2A deletions in 9p and one case with deletion on 3p (the gene RBMS3) were also detected in the tumors. Conclusion SNP arrays provide useful tools for high-resolution characterization of significant chromosomal rearrangements in neuroblastoma tumors. The mapping arrays from Affymetrix provide both copy number and allele-specific information at a resolution of 10–12 kb. Chromosome 9p, especially the gene CDKN2A, is subject to homozygous (four cases) and heterozygous deletions (five cases) in neuroblastoma tumors.